(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
IgA vasculitis (Henoch–Schönlein purpura) is a common pediatric vasculitis characterized by systemic inflammation and multi-organ involvement. Despite its prevalence, little is known about the relationship between disease characteristics, autonomic nervous system dysfunction, and health-related quality of life in affected children. Understanding these associations is crucial for optimizing patient management and improving long-term outcomes. To evaluate the impact of disease form, duration, and severity on autonomic nervous system function and quality of life in children with IgA vasculitis. Fifty children with IgA vasculitis (age range 5–11 years) were assessed. Disease characteristics, including clinical form, duration, and severity, were recorded. Autonomic nervous system function was evaluated using the Pediatric Autonomic Symptom Score (PASS), while quality of life was measured with the Pediatric Quality of Life Inventory (PedsQL). Patients were stratified according to disease form, duration (<1 year, 1–2 years, >2 years), and severity (mild, moderate, severe), and correlations between autonomic dysfunction and quality of life were analyzed. The study revealed a significant association between disease characteristics and autonomic dysfunction. Children with abdominal and mixed forms, longer disease duration, and more severe clinical course demonstrated higher PASS scores, indicating more pronounced autonomic imbalance. Quality of life scores progressively decreased with increasing disease duration and severity, particularly in physical and school functioning domains. A moderate-to-strong inverse correlation was observed between PASS and PedsQL scores, highlighting that increased autonomic dysfunction is associated with decreased quality of life. Disease form, duration, and severity are key determinants of autonomic dysfunction and reduced quality of life in children with IgA vasculitis. Comprehensive assessment, including evaluation of autonomic function and quality of life, is essential for early identification of at-risk patients and for optimizing management strategies. These findings underscore the importance of integrating functional assessments into routine clinical care for pediatric vasculitis.